Comparative Analysis of Teaching with Electronic Media and Conventional Teaching in the Classroom - Abdul Syahid; Florence Angelaila Fauzi; Sumarni Sumarni; Rahmania Ananda; Amanda Salsabila; Azizatun Hafizah; Aprillia Anggraini; Muhammad Romdoni (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The rapid development of educational technology presents new opportunities for enhancing the teaching and learning process through electronic media, which can make learning more interesting and interactive, thus increasing student motivation and engagement. This study aimed to evaluate the effectiveness of different teaching methods direct teaching and the use of audio-visual media in enhancing English language comprehension among fifth grade students at SD Muhammadiyah Pahandut, Palangka Raya. The research involved a service activity conducted with lecturers and students from the Tadris English Education Study Program (TBI) IAIN Palangka Raya. The methodology included both pre-service preparations and the implementation of two distinct teaching approaches. Class 5A received direct teaching with active interaction, while Class 5B utilized interactive videos. The study revealed that conventional teaching in Class 5A faced challenges such as reduced student engagement and passive participation. However, strategic improvements in teaching techniques and classroom management were recommended to enhance effectiveness. In contrast, the use of technological media in Class 5B resulted in higher student engagement and better comprehension of the material, as evidenced by their active participation and correct responses during activities. Overall, the study highlights the advantages and disadvantages of both teaching methods, emphasizing that the choice of method should be context-specific and aligned with learning objectives and student characteristics. The findings suggest that integrating technological media can significantly enhance the learning experience and outcomes, particularly for elementary school students.